Augmented Reality-Based Lactic Acid Bacteria Diversity Flash Card Traditional Pakati'ng Rape’ Food - Raden Salwa; Hanum Mukti Rahayu; Ari Sunandar (Jurnal Pendidikan dan Pengajaran, 2023)
The impact of the Industrial Revolution 4.0 on education is to position education for modern learning. Modern learning must certainly involve learning media that can optimize the learning process. This study aims develop flash card media of lactic acid bacteria diversity of traditional food Pakati’ng Rape’ based on augmented reality. This research uses a research and development (R&D) method with the Alessi and Trollip development model and involves 9 validators to validate flash card learning media. This research instrument uses validation sheets consisting of language validation sheets, media validation sheets and material validation sheets with quantitative analysis techniques. For the practicality test, there is a student response questionnaire instrument. The results of this study are the development of flash card media diversity of lactic acid bacteria traditional food Pakati’ng Rape’ based augmented reality has been declared feasible with an average of 90.39% (is very practical). Based on the result of student responses, the average wa 79% (practical) in the small-scale test and 80% (practical) in the large-scale test. Flash card media diversity of lactic acid bacteria tradisional food Pakati’ng Rape’ based on agumented reality to be valid and practical so that it can be used in learning.